A comparison on isothermal and thermomechanical fatigue behavior of 316LN stainless steel with various tension dwell time. (May 2023) - Wang, Qingtong; Li, Bingbing; Zhao, Jingwei; Itoh, Takamoto; Chen, Xu
Highlights: Effects of various strain hold time on creep-IF and creep-TMF behavior is comparatively studied. Average KAM value is an effective parameter for evaluating accumulation of creep-fatigue damage. Creep-TMF accelerates dislocation configuration evolving into more stabilized wavy-type substructures. More creep damage accumulation in creep-TMF causes a shorter life than creep-IF at hold time of 1800 s. Abstract: Isothermal and thermomechanical fatigue tests with various tension dwell time (designated as creep-IF and creep-TMF respectively) were conducted. The cyclic stress response and stress relaxation behavior were qualitatively and quantitatively discussed based on TEM and EBSD characterization. The fatigue dominated transgranular crack initiation and propagation led to specimen fracture in all creep-IF tests. The transition of dominant damage mechanism from fatigue to creep-fatigue interaction occurred when dwell time increased to 1800 s in creep-TMF test, which caused the intergranular fracture mode and a much shorter life than creep-IF. Moreover, the life prediction model based on tension strain energy was proposed.